1986
DOI: 10.1002/chin.198649282
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: Magnetic Exchange Interactions in Some Novel p‐Azido‐Bridged Copper(II) Dimers.

Abstract: The title Compounds (I)‐(IV) are prepared by reaction of Cu(II) perchlorate hexahydrate or Cu(II) acetate in aqueous solution with the triazacyclononane and sodium azide.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
20
0

Year Published

1997
1997
2014
2014

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 1 publication
2
20
0
Order By: Relevance
“…This value contrasts that for the strongly antiferromagnetic coupled system [(tacn)Cu(μ 2 -1,3-N 3 )(ClO 4 )] 2 (tacn = N,NЈ,NЈЈ-trimethyl-1,4,7-triazacyclononane) with a J value of about -400 cm -1 . [50] The molecular orbitals housing two unpaired electrons are plotted in Figure 6 and clearly show non-orthogonality of the vanadium d orbitals (xz and yz) in the α and β subspaces, consistent with an antiferromagnetically coupled system. The minor overlap between the metal and azide ligand orbitals reflects the observed low-magnitude J value accounting for the weakly antiferromagnetically coupled divanadium centers.…”
Section: Spectroscopic and Magnetization Studies Of Azide Complexes 1mentioning
confidence: 81%
See 1 more Smart Citation
“…This value contrasts that for the strongly antiferromagnetic coupled system [(tacn)Cu(μ 2 -1,3-N 3 )(ClO 4 )] 2 (tacn = N,NЈ,NЈЈ-trimethyl-1,4,7-triazacyclononane) with a J value of about -400 cm -1 . [50] The molecular orbitals housing two unpaired electrons are plotted in Figure 6 and clearly show non-orthogonality of the vanadium d orbitals (xz and yz) in the α and β subspaces, consistent with an antiferromagnetically coupled system. The minor overlap between the metal and azide ligand orbitals reflects the observed low-magnitude J value accounting for the weakly antiferromagnetically coupled divanadium centers.…”
Section: Spectroscopic and Magnetization Studies Of Azide Complexes 1mentioning
confidence: 81%
“…This phenomenon has been reported for dinuclear μ-1,3-N 3 -bridged metal-azide complexes. [50,53] However, our solution magnetic data at 298 K cannot rule out some minor degree of dissociation to mononuclear [(nacnac)V(N 3 )(OAr)] at room temperature. When heated to 100°C, complex 1 is converted to mononuclear nitride [(nacnac)VϵN(Ntol 2 )] (3) in 46 % yield, after recrystallization of the mixture from n-hexane at -37°C (Scheme 2).…”
Section: Introductionmentioning
confidence: 93%
“…[20,25] In the last five years, this picture has changed somewhat because more azido-bridged copper(II) dinuclear complexes have been reported. Some asymmetric EO systems [11][12][13] have now been found that exhibit antiferromagnetic Cu À Cu interactions, while several cases of ferromagnetic couplings have been reported for asymmetric EE systems.…”
mentioning
confidence: 97%
“…[28] Thus, the strong antiferromagnetic interaction of symmetric EE systems was ascribed to the six-coordinate environment of the copper(II) ions with the two bridging azido groups favoring strong overlap between the d x 2 Ày 2 magnetic orbitals. [20,25] In the case of asymmetric EE systems, in which the copper generally has a square-pyramidal geometry, one terminal azido nitrogen atom points to the d x 2 Ày 2 magnetic orbital of one copper and the other to the d z 2 orbital of the second copper. This, combined with the long apical Cu À N azido bonds, was believed to give negligible interactions for pure square-pyramidal geometries that become sizeable antiferromagnetic interactions when the system evolves to a trigonal-bipyramidal geometry.…”
mentioning
confidence: 99%
See 1 more Smart Citation